A distal forearm fracture in childhood is associated with an increased risk for future fragility fractures in adult men, but not women. (18th July 2013) - Amin, Shreyasee; Melton, L Joseph; Achenbach, Sara J; Atkinson, Elizabeth J; Dekutoski, Mark B; Kirmani, Salman; Fischer, Philip R; Khosla, Sundeep
ABSTRACT: Distal forearm fractures are among the most common fractures during childhood, but it remains unclear whether they predict an increased fracture risk later in life. We studied a population‐based cohort of 1776 children ≤18 years of age, from Olmsted County, MN, USA, who had a distal forearm fracture in 1935–1992. Incident fractures occurring at age ≥35 years were identified through review of complete medical records using the linkage system of the Rochester Epidemiology Project. Observed nonpathologic fractures resulting from no more than moderate trauma (fragility fractures) were compared with expected numbers estimated from fracture site–specific incidence rates, based on age, sex, and calendar year, for Olmsted County (standardized incidence ratios [SIR]). In 1086 boys (mean ± SD age; 11 ± 4 years) and 690 girls (10 ± 4 years) followed for 27, 292 person‐years after the age of 35 years, subsequent fragility fractures were observed in 144 (13%) men and 74 (11%) women. There was an increased risk for future fragility fractures in boys who had a distal forearm fracture (SIR, 1.9; 95% CI, 1.6–2.3) but not girls (SIR, 1.0; 95% CI, 0.8–1.2). Fragility fractures at both major osteoporotic (hip, spine, wrist, and shoulder) sites (SIR, 2.6; 95% CI, 2.1–3.3) and remaining sites (SIR, 1.7; 95% CI, 1.3–2.0) were increased in men, irrespective of age at distal forearm fracture as boys. A distal forearm fracture in boys, but not girls, is associated with an increased risk for fragility fractures as older adults. It is necessary to determine whether the increased fractures observed in men is due to persistent deficits of bone strength, continued high fracture risk activity, or both. Until then, men should be asked about a childhood distal forearm fracture and, if so, warrant further screening and counseling on measures to optimize bone health and prevent fractures.